Public Relations of Disposable Groups Using The Example Of The Prison Service - Iwona OSMOLSKA (Communications of International Proceedings, 2024)
Public relations (PR) activities in the Prison Service have a different hierarchy of objectives from the traditional marketing approach. The priority is to show the public the organisation's activities and their benefits, as the institution serves the public and is publicly funded. The publication presents the essence of public relations, its definitional approach, the specifics of the prison guard profession and the public relations activities carried out by the press and information services of the Prison Service. The main objective of the work focuses on the analysis of public communication activities and the diagnosis of the degree of their professionalism. The paper uses both theoretical and empirical research methods, including literature analysis, analysis of activities undertaken by the Prison Service and inference as a cognitive factor in the analysis of the issue. At the same time, the paper attempts to answer the question - based on the results of individual questionnaire surveys - what public relations tools influence the formation of a positive image of the Prison Service? The results of the research indicate that factors such as guards' interpersonal skills, clear and transparent information about the functioning of the institution and communication with the environment determine the positive image of penitentiary units. At the same time, it can be concluded that a positive image is derived from the effectiveness of its activities in ensuring public safety.
Keywords: public relations; image; prison guard.